Character Building in History Learning in Schools Upper-Intermediate (SMA) in Rural and Urban Areas in the Regency Cilacap - Astuti, Wigi (Universitas Negeri Semarang, 2019)
The purpose of this research is (1) to know the development of history-oriented learning planning on character education at SMA in rural and urban areas in Cilacap Regency, (2) to explain the implementation of character education in history learning at SMA in rural and urban areas in Cilacap regency, and (3) to know the historical learning assessments developed by teacher-oriented character education at SMA in rural and urban areas in Cilacap regency. This research uses a qualitative approach with research locations in SMA Negeri 1 Jeruklegi and SMA Negeri 1 Cilacap. Informants were teachers, principals, students of the curriculum, and students from both schools. Data collection techniques are observation, interviews, and documentation. The results show that learning planning made by history teachers in both schools shows that learning tools have been developed by integrating character values. The history teacher implements character education in history learning by incorporating it into the learning process. Character-oriented judgments are conducted through observations during learning activities and in school environments.